2019
DOI: 10.1002/mp.13831
|View full text |Cite
|
Sign up to set email alerts
|

Integral quality monitor (IQM®) signal correction factors for small fields to predict larger irregular segment output signals

Abstract: Purpose To develop a method of correcting for the inaccuracies of small adjoined field segments in their contribution to larger fields in order to get a better match between their combined signals and the measured integral quality monitor (IQM) open field signals. This would enable the pre‐calculation of known irregular segment output signals per monitor unit (MU), which would be later useful for patient‐based dose calculations for treatment verification during pre‐treatment treatment validation using the IQM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[ 46 , 47 ] Shiba et al [ 48 ] revealed that low number of segments will increase the gamma passing rates. Some authors [ 49 51 ] reported that a high percentage of small-area segments can result in a decrease in the gamma passing rates, because small-area segments will lead to the insufficient scattering and insufficient resolution of the detector. Some studies [ 52 , 53 ] had found that the high dose rates, the MU controller communication delay and the low two-dimensional matrix sampling frequency will lead to the dose deviation of small-MU segments.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 , 47 ] Shiba et al [ 48 ] revealed that low number of segments will increase the gamma passing rates. Some authors [ 49 51 ] reported that a high percentage of small-area segments can result in a decrease in the gamma passing rates, because small-area segments will lead to the insufficient scattering and insufficient resolution of the detector. Some studies [ 52 , 53 ] had found that the high dose rates, the MU controller communication delay and the low two-dimensional matrix sampling frequency will lead to the dose deviation of small-MU segments.…”
Section: Discussionmentioning
confidence: 99%
“…The REA collects integral signals from multiple points at the edges of the electrode to provide spatial information about the shape of the beam. REA measures multiple signals that are collected from a single large electrode, which is similar to the way segmented monitor chambers and integral quality monitor (IQM) operate (Valdes 1954, Sjögren et al 1999, Mahuvava and Du Plessis 2019, Oderinde and Plessis 2019, McCaw et al 2020. Segmented monitor chambers are used in accelerator beamlines to control dose rate, flatness, and symmetry thanks to their specific segmentation suitable for derivation of these clinical parameters (Valdes 1954, Sjögren et al 1999, McCaw et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Segmented monitor chambers are used in accelerator beamlines to control dose rate, flatness, and symmetry thanks to their specific segmentation suitable for derivation of these clinical parameters (Valdes 1954, Sjögren et al 1999, McCaw et al 2020. Similarly, IQM has positional sensitivity for linac QA and IMRT fields due to its angled electrodes along the axis of the MLC motion (Mahuvava andDu Plessis 2019, Oderinde and. However, in REA the discrimination of radiation fields is achieved not via segmentation or angling (differential sensitivity to x-rays) but rather via the finite resistance of the collecting electrode.…”
Section: Introductionmentioning
confidence: 99%